Human and Drosophila cryptochromes are light activated by flavin photoreduction in living cells. - Hoang, N.; Schleicher, E.; Kacprzak, S.; Bouly, J.P.; Picot, M.; Wu, W.; Berndt, A.; Wolf, E.; Bittl, R.; Ahmad, M. (PLoS Biology, 2008)
Cryptochromes are a class of flavoprotein blue-light signaling receptors found in plants, animals, and humans that control plant development and the entrainment of circadian rhythms. In plant cryptochromes, light activation is proposed to result from photoreduction of a protein-bound flavin chromophore through intramolecular electron transfer. However, although similar in structure to plant cryptochromes, the light-response mechanism of animal cryptochromes remains entirely unknown. To complicate matters further, there is currently a debate on whether mammalian cryptochromes respond to light at all or are instead activated by non-light-dependent mechanisms. To resolve these questions, we have expressed both human and Drosophila cryptochrome proteins to high levels in living Sf21 insect cells using a baculovirus-derived expression system. Intact cells are irradiated with blue light, and the resulting cryptochrome photoconversion is monitored by fluorescence and electron paramagnetic resonance spectroscopic techniques. We demonstrate that light induces a change in the redox state of flavin bound to the receptor in both human and Drosophila cryptochromes. Photoreduction from oxidized flavin and subsequent accumulation of a semiquinone intermediate signaling state occurs by a conserved mechanism that has been previously identified for plant cryptochromes. These results provide the first evidence of how animal-type cryptochromes are activated by light in living cells. Furthermore, human cryptochrome is also shown to undergo this light response. Therefore, human cryptochromes in exposed peripheral and/or visual tissues may have novel light-sensing roles that remain to be elucidated.